2000
DOI: 10.1056/nejm200008173430702
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Levels of Factor VIII and the Risk of Recurrent Venous Thromboembolism

Abstract: Patients with a high plasma level of factor VIII have an increased risk of recurrent venous thromboembolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
478
8
14

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 696 publications
(522 citation statements)
references
References 26 publications
22
478
8
14
Order By: Relevance
“…Moreover, during the entire follow-up period, only 58 thrombotic recurrences (Ϸ9.7% of patients) were recorded; this figure is lower than might be expected, although it is similar to those reported in other studies. 23 An Italian collaborative study showed that no long-term clinical benefit was associated with extending the 3-month course of anticoagulant treatment to 1 year in patients with idiopathic proximal DVT. In fact, prolongation of anticoagulation only delays recurrences until anticoagulation is stopped and does not reduce the risk of recurrence.…”
Section: Palareti Et Al D-dimer and Vte Recurrence 315mentioning
confidence: 99%
“…Moreover, during the entire follow-up period, only 58 thrombotic recurrences (Ϸ9.7% of patients) were recorded; this figure is lower than might be expected, although it is similar to those reported in other studies. 23 An Italian collaborative study showed that no long-term clinical benefit was associated with extending the 3-month course of anticoagulant treatment to 1 year in patients with idiopathic proximal DVT. In fact, prolongation of anticoagulation only delays recurrences until anticoagulation is stopped and does not reduce the risk of recurrence.…”
Section: Palareti Et Al D-dimer and Vte Recurrence 315mentioning
confidence: 99%
“…By preference such a predictor is not influenced by use or type of anticoagulants, optimizing the applicability of the assessment model. Candidate coagulation factors are factor (F)VIII, von Willebrand factor (VWF), and d ‐dimer for which higher levels are associated with increased recurrence risk 3, 4, 5, 6, 7. Preferably, risk assessment and herewith the measurement of these coagulation factors is performed while the patient is still on anticoagulant treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of coagulation factor (FVIII) are an important risk factor for venous thrombosis [1][2][3][4]. FVIII activity (FVIII:C) ‡150 IU dL )1 increases the risk of a first venous thrombosis 5-fold compared to levels below 100 IU dL )1…”
mentioning
confidence: 99%